HUBUNGAN KESADARAN BERAGAMA DENGAN SIKAP SOSIAL SISWA DI SMP N 1 KEC. HARAU - Venna Yolanda; Intan sari; Dodi Pasila Putra; Arjoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the relationship between religious awareness and students' social attitudes. This study used a quantitative approach with a correlational research type, with a population of 310 students. The sampling technique used proportional random sampling. The sample size was 175 students. Data analysis was conducted to test the research hypothesis using simple linear regression using SPSS 25. The results of this study indicate a positive relationship between religious awareness and students' social attitudes. This illustrates that the higher the religious awareness, the higher the students' social attitudes. Social attitudes have a 64 % influence on students' social attitudes, with a significance level of 0.000 <0.05 and a t-test value of 10,950 > 1.97718. Therefore, it can be interpreted that religious awareness is related to students' social attitudes.